To the Issue of the WTO Dispute Settlement Practice on Subsidies - I. O. Danilov (Московский журнал международного права)
As acknowledged on numerous occasions by various international trade experts and practitioners, the existing WTO dispute settlement system works quite satisfactorily. This system is largely based upon past GATT-1947 practice on dispute settlement. The WTO Dispute Settlement Understanding (DSU) is nowadays the principal WTO Agreement applicable to the resolution of trade disputes arising among WTO Members.The DSU, however, is regularly criticised by various stakeholders for certain shortcomings, including, inter alia, «weak» enforcement disciplines partially inherited from the «old» GATT’ dispute resolution practice.In this respect, the reliance by WTO Panels and the Appellate Body in their recommendations on exclusively prospective remedies for injured WTO Members is certainly questionable and has given rise to interesting discussions from the legal, political as well as economic points of view.This is particularly true with regard to disputes involving subsidies, where special provisions on dispute resolution of the WTO Agreement on Subsidies and Countervailing Measures (ASCM) apply and which under certain conditions supersede the respective DSU rules In this respect, the author argues that in cases where Articles 4 7 or 7 8 of the ASCM, which deal with remedies available to counter certain illegal subsidization practices, apply, the WTO Dispute Settlement Panels as well as the Appellate Body are entitled to have recourse to retroactive remedies and to recommend repayment (even in full in certain cases) by recipients of illegally provided subsidies.While the «retroactivity of remedies» approach is not supported by the prevailing WTO dispute settlement practice and current views of certain WTO Members, it has basis under the legal texts of both DSU and ASCM.Its admissibility has also been indirectly confirmed in reports of GATT/WTO Panels and could be supported by statements of certain other WTO Members In addition, this kind of approach would be in line with customary rules of public international law on state’s responsibility.However, the introduction of retrospective remedies into WTO dispute settlement practice would give considerably more weight to the judicial and technical components of the WTO dispute settlement mechanism.This would certainly diminish the political and negotiations-based nature of the current WTO dispute settlement proceedings. That, in turn, may trigger an evolution of the enforcement procedures of the WTO dispute settlement process to purely law-based procedures, similar to national or international commercial courts, and to abandoning their current «quasijudicial» status.